If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2.5x+15 + 0.5(x-4)=1.2x+2(0.5x-6)
We simplify the equation to the form, which is simple to understand
2.5x+15 + 0.5(x-4)=1.2x+2(0.5x-6)
Reorder the terms in parentheses
2.5x+15+( + 0.5x-2)=1.2x+2*(0.5x-6)
Remove unnecessary parentheses
+2.5x+15 + 0.5x-2=+1.2x+2+*( + 0.5x-6+)
Reorder the terms in parentheses
2.5x+15 + 0.5x-2=1.2x+(+1x-12)
Remove unnecessary parentheses
+2.5x+15 + 0.5x-2=+1.2x+1x-12
We move all terms containing x to the left and all other terms to the right.
+2.5x + 0.5x-1.2x-1x=-12-15+2
We simplify left and right side of the equation.
+ 0.8x=-25
We divide both sides of the equation by 0.8 to get x.
x=-31.25
| 4(2y+9)+7y= | | 7(x+2)=7x+2 | | (5x+3-2)(8-2x+1)= | | 9-.333g=13 | | 2x^2+9x=5 | | .25f=8-3 | | 3(4x-3)+2x=89 | | .25f+3=8 | | 3(4x+3)=68 | | 2(x+5)-10=8 | | 4x-20=7x+14 | | 15m-2(3+5m)= | | 15x^2-50y+35=0 | | 2-(8p-q)-7(p+6)+4q= | | -8x+x^2=-12 | | x^2-x-20=0 | | 7(p+3)=7b-4 | | f(11)=1/2(11)+5 | | 9(s+7)-(7s+m)-9m= | | f(11)=2(11)+5 | | 9(7x+8)+3(x+-10)= | | 7x+9=-11x+12 | | 7x+9and=-11x+12 | | -(9q+7)+3(2q-5)= | | 8y-2=14y-3 | | 20-4(w+1)=9w-4(9+w) | | 3(s-5)-7(4s-7)= | | 2x+40=90 | | wx=-4 | | P=a+2 | | 9x-(-6x-6)=-24 | | -2-(6t+9)= |